Did COVID-19 Exacerbate the ‘Day-of-the-Week Effect’ in the Nasdaq, S&P 500, and Russell 2000 Stock Markets? - Zhao, Hongyu (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
The presence of seasonal patterns in the returns and volatility of various international stock exchanges may indicate the lack of integration in financial markets. Consequently, such abnormal behaviors can create investment opportunities. This paper investigates this type of anomaly, specifically analyzing the ‘day-of-the-week effect’ in the Nasdaq, S&P 500, and Russell 2000 markets through a dummy regression model. The results indicate no unusual behavior in the returns of these stock markets. The day-of-the-week effect was not influenced by the outbreak of COVID-19.